Design Requirements for a PID and FLC for a Single Inverted Pendulum Using VHDL - داود, محسن; نعمان, زياد; ديوب, علي (Latakia University Journal -Engineering Sciences Series, 2021)
Control systems with different strategies have emerged as one of the most promising areas for industrial applications. The significant growth in control system applications has led to the need to find an efficient method of instrument implementation . Field Programmable Gate Array (FPGA) is the most important hardware implementation tool due to its low power consumption, high operating speed and large capacity for data storage. In this article, instead of presenting a methodology for traditional PID and modern FLC control systems, we showed the implementation of both PID and FLC using Very Hardware Description Language (VHDL) code. PID and FLC are designed to control the angle of the inverted pendulum . VHDL was used for programming PID and FLC on FPGA. Simulated controller algorithms were implemented on the FPGA Cyclone II EP2C5T144C6 Board